The Profile of Cataract Patients at the Eye Polyclinic of PKU Muhammadiyah Hospital Rogojampi - Ayu Dyah Annisha (Jurnal Kesehatan Masyarakat Celebes, 2022)
Cataracts are the second leading cause of blindness in the world after uncorrected refractive errors. In Indonesia, the blindness rate based on the 2014-2016 RAAB survey found the prevalence of blindness from 15 provinces ranged from 1.4% in West Sumatra and 4.4% in East Java. Cataract is a clouding of the intraocular crystalline lens where this cloudiness can lead to decreased vision function and can lead to blindness, while blindness caused by cataracts is preventable blindness. The purpose of this study was to identify and collect data on the frequency of cataract patient profiles at the Eye Polyclinic of PKU Muhammadiyah Rogojampi Hospital in 2021. The method applied in this study was a retrospective descriptive study by applying a cross-sectional approach. The data of this study were obtained from secondary data, namely medical record examination at PKU Muhammadiyah Rogojampi Hospital. This study was conducted during June-October 2021. The population used in this study were all cataract patients at PKU Muhammadiyah Rogojampi Hospital with a sample of 41 respondents. Data analysis with univariate is shown in the frequency distribution table. The results indicated that from 41 respondents, 19 people (46%) were in the age range of 60-69 years, while 26 people (63%) were male, and there were 12 people (29%) who worked as farmers.